ОСОБЛИВОСТІ ПРАКТИЧНОГО ВИКОРИСТАННЯ АВТОНОМНИХ ДІАГНОСТИЧНИХ КОМПЛЕКСІВ ДЛЯ ТЕПЛОВОГО КОНТРОЛЮ ПОВІТРЯНИХ ЛІНІЙ ЕЛЕКТРОПЕРЕДАЧІ - Бабак, С.В.; Мислович, М.В. (Інститут електродинаміки НАН України, Київ, 2016)
Using thermal imaging equipment, installed on unmanned quadrocopter, experimental researches of temperature condition of the overhead power transmission line wires were conducted. Provided an example of spline functions statistical method application for prediction of time interval where, under certain conditions, it is possible to reach unacceptable temperatures for studied overhead power transmission line wires. References 14, table 1, figures 4.